Toxicidade reprodutiva e resposta de múltiplos biomarcadores no caramujo Biomphalaria glabrata (Say 1818) após exposição crônica às nanopartículas de óxido de ferro (γ-Fe2O3) funcionalizadas com ácido glucônico - Caixeta, Maxwell Batista (2020)
Nanotechnology has been applied to control parasites and intermediate hosts of etiologic agents of neglected global and tropical diseases, such as schistosomiasis. The parasite Schistosoma mansoni is the etiological agent of this disease in Brazil, and snails Biomphalaria spp. act as intermediate host. The use of nanomaterials (NMs) as molluscicidal agents is promising due to their specific properties that allow internalization, greater reactivity and specificity to the snail, in addition to the ease of production, and the possibility of removal from the environment. In this sense, the aim of this work was to evaluate the potential molluscicidal activity of gluconic acid - functionalized iron oxide nanoparticles (IONPs) in the snail Biomphalaria glabrata. Initially, a bibliometric analysis associated with a systematic review of the literature identified that different NMs were able to induce oxidative stress, genotoxicity, mutagenicity, embryotoxicity, reproductive and transgenerational toxicity, immunotoxicity, mortality and behavioural changes in different species of gastropods. Regarding bioassays, after chronic exposure (28 days) of B. glabrata to different concentrations of IONPs and FeCl3 (1.0; 2.5; 6.2 and 15.6 mg L-1), a high bioaccumulation of iron by IONPs in visceral mass of the snail compared to the iron ions and the control group was observed. Likewise, there was a high frequency of behavioural changes in snails exposed to IONPs when compared to their ionic counterpart and to the control group. Both forms of Fe reduced fertility, while mortality and reduced snail’s fertility were observed only after exposure to IONPs at 15.6 mg L-1. The general results indicated behavioural impairments and reproductive toxicity, associated with the bioaccumulation of IONPs in B. glabrata. This study emphasizes that metal-based nanoparticles are potential molluscicidal agents.